Teaching macroeconomics with Microsoft Excel - Barreto, Humberto, 1960- (New York : Cambridge University Press, 2016)
Humberto Barreto gives professors a simple way to teach fundamental concepts for any undergraduate macroeconomics course using Microsoft Excel® with Excel workbooks and add-ins and videos freely available on his university website. The Excel files are designed to be used by students with any textbook, and have been used many times by the author in his own teaching. Each Excel workbook contains links to short screencasts, around five to ten minutes, that show the cursor and typing as the file is manipulated with narration that walks the student through the steps needed to complete a task. The book shows professors a simple way to present macroeconomic models and incorporate data into their courses.
Title from publisher's bibliographic system (viewed on 05 May 2016).
Keywords: Macroeconomics -- Study and teaching; Microsoft Excel (Computer file)